Feminization of Agriculture in China : Debunking the Myth and Measuring the Consequence of Women Participation in Agriculture - Zhang, Linxiu (World Bank, Washington, DC, 2012)
This paper helps build a clear picture of the role of women in China's agriculture and, if agricultural feminization has been occurring, its impact on labor use, productivity, and welfare. Using two data sets that track changes in labor use over time, the authors examine the evolution of off farm and on farm employment trends and analyze the role of men and women in the emergence of China's labor markets. They explore who is working on China's farms, and the effects of these decisions on labor use, productivity and welfare. The analysis debunks the myth that China's agriculture is becoming feminized. Even if women were taking over the farm, the consequences in China would be mostly positive from a labor supply, productivity and income point of view. There may be some lessons for the rest of the world on what policies and institutions help make women productive in a nation's agricultural sector. Policies that insure equal access to land, regulations that dictate open access to credit, and economic development strategies that encourage competitive and efficient markets all contribute to an environment in which women farmers can succeed.